Dynamics of EUV-radiation from the partially contracted plasma diode - Hrechko, Ya.O.; Azarenkov, N.A.; Dimitrova, V.D.; Borgun, Ie.V.; Ryabchikov, D.L.; Sereda, I.N.; Hryhorenko, A.V.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2015)
The possibility of forming the directional plasma extreme ultraviolet (EUV) radiation under the partial contraction of the current channel by the dielectric insert in a high-current plasma diode is studied. The discharge characteristics and their impact on the dynamics of the radiation in the wavelength range of 12.2…15.8 nm are studied. The input efficiency of energy in the discharge is higher one in the case of partial contraction of the current channel by the dielectric insert which leads to an increase of the EUV-radiation intensity.